Kepemimpinan Kepala Sekolah dalam Mengembangkan Pembelajaran Pendidikan Agama Islam (PAI) - Khumairoh An Nahdliyah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2018)
The principal has his own main duties and functions. Without the principal, it is impossible for the school to run well. Therefore, in choosing school leaders it must be truly competent, wise and fair because every leader will be held accountable. Islam views that leadership must be held by someone capable and able to position themselves as obar of truth by setting a good example, because he is uswatun hasanah. The role of the principal is very important, a principal must be able to plan and implement work programs, as well as conduct periodic evaluations of the educational process. As Educators always hold evaluation meetings of all the teachers, As the Manager Principal's controls the students in the learning process through the picket teacher, As the Administrator Principal develops PAI learning through MGMP of religious teachers, As Supervisor The principal conducts supervision activities to improve teacher professionalism. As Leader the headmaster applies KTSP. As an innovator the principal implements three curricula, but the special subjects of PAI stand alone with an allocation of 2 JP / week. As The motivator principal's provides convenient facilities for students